(untitled) (JED (Jurnal Etika Demokrasi), 2023)
Fishermen in the lower middle-class suburbs experience uncertain conditions, low income, low education levels, marketing of their catches that are still declining, and erratic weather that causes disruption to the economic life of the fishing community. The purpose of this research is to analyze the livelihood structure strategy of peripheral fishermen towards the dynamics of fishermen in Pasie Nan Tigo Village, Padang City. The type of research used is descriptive using a qualitative approach. Data collection methods are carried out in several ways, namely observation, interviews, and data collection or documentation. This research uses analysis from the Milis and Hubermen model which divides several stages, namely data collection, data reduction, data presentation and conclusion drawing. The results of this study show that the livelihood structure of the fishing community is very diverse, namely dual livelihood strategies and diversification of fishing gear. The level of technology used is still modern and traditional technology. In the upper middle class fishing community using modern technology tools, while the lower middle class only uses traditional tools and there is a wage sharing system that is carried out every day afterwards. The conclusion of this study is that the structure of livelihood determines the actions and layers of society.